Prevalence and predictors of short stature in children aged 3–18 years in Hainan Province, China: a cross-sectional study - Yan, Mi; Qin, Yingying; Li, Hongai; Huang, Chuican; Li, Haidan; Liu, Li; Cai, Yuhua; Fan, Lichun; Xiang, Wei; Huang, Xiaoyan (Frontiers in Pediatrics, 2025)
BackgroundShort stature is a global health-related problem and remains to be evaluated in children in Hainan Province. The present study was conducted to investigate the associated factors with short-stature in children.MethodsThis cross-sectional study was conducted using a staged, cluster random sampling method. A total of 26,189 children aged 3–18 years, originating from 18 cities and counties in Hainan Province, to determine the prevalence of short stature. Additionally, these children were selected for a thorough analysis of associated factors.ResultsThe crude prevalence of short stature was 2.88%, and the standard prevalence was (after adding weights) 3.01%. Children's short stature was significantly related to seven factors: area, birth weight, body mass index z score (BAZ), maternal education, family income (RMB per year), frequency of bean intake and frequency of egg intake. A nomogram model of factors associated with short stature was constructed. The area under the curve (AUC) of the receiver operating characteristic (ROC) curve was 0.698 (95% CI: 0.679–0.716).ConclusionsOur findings demonstrated that birth weight, BAZ, dietary habits, and family-related factors were strongly correlated with short stature in children in Hainan Province.